On proving syntactic properties of CPS programs - Danvy, Olivier; Dzafic, Belmina; Pfenning, Frank (BRICS Report Series, 1999)
Higher-order program transformations raise new challenges for proving properties of their output, since they resist traditional, first-order proof techniques. In this work, we consider (1) the "one-pass" continuation-passing style (CPS) transformation, which is second-order, and (2) the occurrences of parameters of continuations in its output. To this end, we specify the one-pass CPS transformation relationally and we use the proof technique of logical relations.